2001
DOI: 10.3201/eid0705.017509
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Redosing of Cefazolin and Risk for Surgical Site Infection in Cardiac Surgery

Abstract: Intraoperative redosing of prophylactic antibiotics is recommended for prolonged surgical procedures, although its efficacy has not been assessed. We retrospectively compared the risk of surgical site infections in 1,548 patients who underwent cardiac surgery lasting >240 min after preoperative administration of cefazolin prophylaxis. The overall risk of surgical site infection was similar among patients with (43 [9.4%] of 459) and without (101 [9.3%] of 1,089) intraoperative redosing (odds ratio [OR] 1.01, 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(48 citation statements)
references
References 14 publications
0
47
0
1
Order By: Relevance
“…In current literature, most of the authors recommend to use within one hour of surgical incision for cephalosporins and can be extended to two hours for vancomycin and fluoroquinolones [74]. In patients with large blood volume loss (>2000 cc) or high volume of fluid resuscitation (>2000cc), and surgery times that last more than two half-lives of the prophylactic agent, an additional intraoperative dose of antibiotics is necessary [78]. …”
Section: The Operation Daymentioning
confidence: 99%
“…In current literature, most of the authors recommend to use within one hour of surgical incision for cephalosporins and can be extended to two hours for vancomycin and fluoroquinolones [74]. In patients with large blood volume loss (>2000 cc) or high volume of fluid resuscitation (>2000cc), and surgery times that last more than two half-lives of the prophylactic agent, an additional intraoperative dose of antibiotics is necessary [78]. …”
Section: The Operation Daymentioning
confidence: 99%
“…In addition to pre-operative hospitalization, our findings add to the existing body of literature showing that failure to re-dose surgical chemoprophylaxis intra-operatively (re-dosing non-compliance) increases the risk for post-operative infection and SSI. [26][27][28][29] Current recommendations include instructions to re-dose prophylactic antibiotics intra-operatively if the duration of the operation exceeds two half-lives of the antibiotic. For example, the half-lives of cefoxitin and piperacillintazobactam are 0.7-1.1 and 0.7-1.2 h, which translate into re-dosing intervals of 2-3 h after the initial dose.…”
Section: Discussionmentioning
confidence: 99%
“…These included: age, race, smoking status, body mass index, malignancy, diabetes, American Society of Anesthesiologists (ASA) physical status, surgical chemoprophylaxis data (type, timing and dose), operative time, blood loss during surgery, an intra-operative red blood cell transfusion and open versus minimally invasive surgery. 7,[20][21][22][23][24][25][26][27][28][29][30] Statistical analysis Bivariate analyses of the association between each variable and exposure to pre-operative hospitalization using the Student's t, Pearson v 2 , and Wilcoxon's rank-sum tests as appropriate were performed. We used univariable logistic regression to calculate unadjusted odds ratios (OR) and 95% confidence intervals (CI) for the association between pre-operative hospitalization and the risk of HAIs and SSIs in particular.…”
Section: Study Design and Patient Selectionmentioning
confidence: 99%
“…Furthermore, the second time-out is a good time to redose antibiotics and draw necessary labs. Reports have shown that redosing of antibiotics significantly decreases the rate of surgical site infections, especially in surgeries which last longer than 4 hours [36,37]. Redosing, however, may be forgotten in longer operations; only approximately one out of five cases with extended surgical times receive antibiotic redosing [37].…”
Section: Methodsmentioning
confidence: 99%